Seeing burnout coming: early signs and recognition strategies in health professionals - Karakolias, Stefanos (Frontiers in Public Health, 2025)
Burnout syndrome is a pervasive psychological condition arising from prolonged occupational stress. Health professionals, particularly those in high-stakes environments, are especially vulnerable due to chronic workplace pressures, high job demands, and limited resources. While the prevalence and risk factors of burnout are well-documented, early warning signs often go unrecognized until the condition becomes chronic. This review synthesizes current evidence from 45 studies published between 2010 and 2025 on the early indicators and recognition strategies of burnout, introducing a three-domain framework for proactive detection. The first domain involves intrapersonal indicators, including emotional, cognitive, and physical symptoms such as persistent fatigue, impaired concentration, poor sleep quality, and physical complaints. The second domain focuses on interpersonal indicators, reflected in depersonalization, irritability, reduced empathy, and expressions of dissatisfaction. The third domain comprises occupational manifestations, ranged from absenteeism, tardiness, and declining job performance to unhealthy overcommitment despite apparent productivity. Effective strategies involve systematic monitoring of behavioral changes, validated assessment tools, predictive analytics, workplace surveys, and tracking of physiological stress markers. Organizational interventions, including supportive leadership, resilience and emotional intelligence training, workload management, and fostering a positive work culture, are crucial. This review emphasizes early recognition as a cornerstone for preventive strategies and underscores the need for evidence-based, proactive policies to safeguard healthcare professionals’ wellbeing and optimize occupational health outcomes.